2004
DOI: 10.1073/pnas.0406398101
|View full text |Cite
|
Sign up to set email alerts
|

A digital technique for art authentication

Abstract: We describe a computational technique for authenticating works of art, specifically paintings and drawings, from high-resolution digital scans of the original works. This approach builds a statistical model of an artist from the scans of a set of authenticated works against which new works then are compared. The statistical model consists of first-and higher-order wavelet statistics. We show preliminary results from our analysis of 13 drawings that at various times have been attributed to Pieter Bruegel the El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 17 publications
1
105
0
2
Order By: Relevance
“…For example, Lyu, Rockmore, and Farid found that real Brueghel drawings can be distinguished from imitations via a variety of statistics of the wavelet coefficients [3]. This approach was further extended to the faces of a Perugino painting thought to be painted by several hands; the three faces that clustered in this analysis agreed with the three that art experts think were painted by the same hand.…”
Section: Previous Worksupporting
confidence: 55%
See 1 more Smart Citation
“…For example, Lyu, Rockmore, and Farid found that real Brueghel drawings can be distinguished from imitations via a variety of statistics of the wavelet coefficients [3]. This approach was further extended to the faces of a Perugino painting thought to be painted by several hands; the three faces that clustered in this analysis agreed with the three that art experts think were painted by the same hand.…”
Section: Previous Worksupporting
confidence: 55%
“…This assumes that an artist's brushwork is characterized by signature features (caused, e.g., by the artist's habitual physical movements) which might be found by machine learning methods and used as an additional piece of evidence to rule upon authenticity. Indeed, early attempts in this area have already found considerable success [2,3,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Finally, quantitative stylometric analyses have long been used to clarify gross relationships between texts. Standard applications of stylometry include dating literary works and resolving questions of attribution (26)(27)(28)(29)(30). Both ad hoc stylometric analysis and supervised machine learning with stylometric features have proven successful for such applications (31)(32)(33), including for cases in Latin literature (34).…”
Section: Significancementioning
confidence: 99%
“…The main focus of the papers is on the artistic identification problem, where the goal is to classify original and fake paintings of a given artist [4,32,39] or to produce stylistic analysis of paintings [20,24,25]. Most of the methods above can be regarded as adaptations from the content-based image retrieval systems [14], where the emphasis is placed on the characterization of brush strokes using texture or color.…”
Section: Literature Reviewmentioning
confidence: 99%